PERSPEKTIF AL-QUR'AN TERHADAP FENOMENA CYBERSEXUAL PADA GENERASI ALPHA - Laila Ilmi, Rizky; Achmad Zayyadi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
The rapid development of digital technology has given birth to a new phenomenon in human sexual behavior, one of which is cybersexual, namely sexual activity based on the virtual world through text, images, sound, or video. This phenomenon is now starting to penetrate Generation Alpha, a young age group that is very familiar with the digital world from an early age. The increasing involvement of Generation Alpha in virtual sexual activities raises concerns about their moral, spiritual, and social future. This study aims to examine the phenomenon of cybersexuality from the perspective of the Qur'an, by emphasizing moral values ​​and relevant sharia commands in fortifying deviant sexual behavior in the digital era. This research approach is qualitative with a library research method that focuses on normative interpretations of the verses of the Qur'an, especially those related to the concept of al-'iffah (maintaining honor), ghadhdh al-bashar (lowering the gaze), and the prohibition of approaching zina. Data were collected from thematic interpretations, Islamic scientific literature, and contemporary studies on the online behavior of the younger generation. The results of the study indicate that Qur'anic values ​​have high relevance in counteracting the negative impacts of cybersexuality by forming spiritual, moral, and digital ethical awareness. In addition, the Qur'an encourages comprehensive protection of the younger generation through a preventive approach based on education and a healthy social environment. The contribution of this study lies in strengthening the role of the Qur'an as a source of transhistorical values ​​that are able to answer the challenges of the times, including the dynamics of sexual behavior in the digital space. This study also encourages the need for the formation of a contextual Qur'anic-based education curriculum for Generation Alpha, as well as opening up space for further empirical studies that are more applicable in preventing cybersexuality among Muslim youth.